Recent advances in biosynthesis mechanisms and yield enhancement strategies of erythritol - Wenli Yang; Xiangying Zhao; Mo Han; Yuchen Li; Yanjun Tian; Zhangbo Rong; Jiaxiang Zhang (Critical Reviews in Food Science and Nutrition, 2024)

Autonomous inspection robot for dead laying hens in caged layer house - Weihong Ma; Xingmeng Wang; Simon X. Yang; Xianglong Xue; Mingyu Li; Rong Wang; Ligen Yu; Lepeng Song; Qifeng Li (Computers and Electronics in Agriculture, 2024)

Path planning of greenhouse electric crawler tractor based on the improved A* and DWA algorithms - Huiping Guo; Yi Li; Hao Wang; Chensi Wang; Jiao Zhang; Tingwei Wang; Linrui Rong; Haoyu Wang; Zihao Wang; Yaobin Huo; Shaomeng Guo; Fuzeng Yang (Computers and Electronics in Agriculture, 2024)

Lipid biomarkers indicate the dynamics of particulate organic carbon and its carbon sequestration effects during the degradation of Ulva prolifera - Miaomiao Zhao; Hongmei Li; Rong Bi; Hailong Zhang; Shengrong Huang; Li Li; Yang Ding; Yongyu Zhang; Meixun Zhao (Marine Pollution Bulletin, 2024)

Effect of long-term temperature-controlled rearing on growth traits and sexual maturity of common carp (Cyprinus carpio) - Yongming Li; Kuangxin Chen; Bin Gui; Cheng Yang; Libo He; Lanjie Liao; Zuoyan Zhu; Yaping Wang; Rong Huang (Aquaculture, 2024)

Scaled experimental study of a ventilation system featuring partition jet and pit exhaust - Qizhi Yang; Xi Bai; Guoqiang Zhang; Li Rong; Yao Tao; Jiyuan Tu; Jinyong Wang; Zhiru Hu; Jie Chai; Yong Wang (Biosystems Engineering, 2024)

Mechanism of antimony oxidation and adsorption using immobilized Klebsiella aerogenes HC10 in soil - Qun Rong; Dingtian Lu; Kai Zhong; Shu Yang; Zhongyi Li; Chaolan Zhang (Science of The Total Environment, 2024)

Invisible hazards: Exploring neonicotinoid contamination and its environmental risks in urban parks across China - Yongfeng Deng; Ruqin Shen; Xue Zhang; Yang Li; Xingguo Chen; Rong-Rong He; Hao Tian; Shuqin Tang; Xiang Luo; Jing Li; Wan-Yang Sun; Hongli Tan (Science of The Total Environment, 2024)

Effects of changing spatial scale on debris-flow hazard assessment: A case study in the Dadu River basin, China - Lili Zhang; Jianqiang Zhang; Zaiyang Ming; Haoyu Li; Rong Chen; Yang Jia (Science of The Total Environment, 2024)

Revealing the links between hair metal(loids) and alterations in blood pressure among children in e-waste recycling areas through urinary metabolomics - Hong-Xuan Kuang; Ye Liu; Jia-Rong Wang; Meng-Yang Li; Yang Zhou; Lin-Xue Meng; Ming-Deng Xiang; Yun-Jiang Yu (Science of The Total Environment, 2024)

Long-term cereal-legume intercropping accelerates soil organic carbon loss in subsoil of dryland - Wei Wang; Guang-Rong Chen; Meng-Ying Li; Yinglong Chen; Yang Wang; Hong-Yan Tao; Hui-Zhi Hou; Muhammad Maqsood Ur Rehman; Muhammad Ashraf; Yajie Song; Levis Kavagi; Bao-Zhong Wang; et al. (Resources, Conservation and Recycling, 2024)

Phylogenomic analyses of the pantropical Platycerium Desv. (Platycerioideae) reveal their complex evolution and historical biogeography - Jing Zhao; Chuan-Jie Huang; Li-Ju Jiang; Zhao-Rong He; Shuai Yang; Zhang-Ming Zhu; Liang Zhang; Hong Yu; Xin-Mao Zhou; Jia-Guan Wang (Molecular Phylogenetics and Evolution, 2024)

Variation profiles, formation mechanisms, and emission risks of brominated flame retardant compounds during cement kiln co-processing of hexabromocyclododecane-containing waste - Xin Li; Yahui Liu; Bingcheng Lin; Guohua Zhu; Jian Wang; Xiao Wang; Yueyao Yang; Shanshan Zhang; Guorui Liu; Rong Jin; Minghui Zheng (Journal of Hazardous Materials, 2024)

Soy protein isolate ameliorate gel properties by regulating the non-covalent interaction between epigallocatechin-3-gallate and myofibrillar protein - Ying Li; Yijun Zhang; Gongchen He; Ziyan Qiao; Rong Yang; Xi Zhou; Lin Chen; Xianchao Feng (Food Chemistry, 2024)

Quality improvement of threadfin bream (Nemipterus virgatus) surimi-gel using soy protein as a natural food additive - Yi-Li Gao; Asami Yoshida; Jin-Yang Liu; Jing Yuan; Shinnosuke Maeda; Youjun Wang; Yan-Rong Jiang; Xiao-Mi Sun; Chao-Ping Chen; Yajun Wang; Tetsuhiko Okajima; Kiyoshi Osatomi (Food Chemistry, 2024)

Migration mechanism of PTEs in polymetallic mines under pioneer phytoremediation: A Lanmuchang mercury-thallium mine perspective - Jichang Wen; Ruijia Yang; Xinlong Li; Rong Xie; Yonggui Wu (Environmental Research, 2024)

Blood cadmium levels and overactive bladder in middle-aged and older adults in the United States: Insights from NHANES 2007–2020 data - Fan Gao; Yin Lu; Qiang Cheng; Qing Ai; Bin Jiang; Zhen-Jun Luo; Guo-Rong Yang; Kai-Kai Lv; Qing Yuan; Hong-Zhao Li (Environmental Pollution, 2024)

Meet-in-metabonomics: Insights into associations between hair heavy metal and adverse child growth in e-waste recycling area - Hong-Xuan Kuang; Meng-Yang Li; Jia-Rong Wang; Jian-Hua Tan; Wen-Yao Liang; Yang Zhou; Yun-Jiang Yu (Environmental Pollution, 2024)

Temperature adaptive passive daytime radiative cooling: The impact of their essential properties on energy performance of different building types - Yujie Yang; Guoqiang Zhang; Li Rong (Energy and Buildings, 2024)

Ultra-low temperature heating system based on dual-source solar assisted heat pump using compound parabolic concentrator-capillary tube solar collector - Li Wei Yang; Jin Huan Pu; Rong Ji Xu; Tong Yang; Hua Sheng Wang (Energy and Buildings, 2024)

MOF-derived S, N co-doped porous carbon matrix with single Fe atoms and CoSx nanoparticles dual-sites for enhanced oxygen reduction - Yu chen; Jian Rong; Jing Wu; Yuzhe Zhang; Huaisheng Ao; Xudong Zheng; Chao Jing; Ruilan Yang; Ziyao Zhou; Zhongyu Li (Chemical Engineering Journal, 2024)

Long-lasting Zn metal anode coated with an industrially available amorphous InGaZnO layer - Jiadong Wu; Linyu Yang; Shuang Zhou; Shuying Wang; Ablat Abliz; Rong Wu; Kunjie Zhu; Xiaolong Yao; Haibing Li; Jun Wang; Hongyu Mi; Jie Li; et al. (Chemical Engineering Journal, 2024)

p-Smad3 differentially regulates the cytological behavior of osteoclasts before and after osteoblasts maturation - Jiapeng Ye; Zhen Hua; Jirimutu Xiao; Yang Shao; Shaoshuo Li; Heng Yin; Mao Wu; Yi Rong; Bowen Hong; Yang Guo; Yong Ma; Jianwei Wang (Molecular Biology Reports, 2024)

The GaKAN2, a KANADI transcription factor, modulates stem trichomes in Gossypium arboreum - Xujiao Ren; Luying Yang; Yasir Muhammad; Yuxing Xie; Xinyi Lin; Li Yu; Yuefen Cao; Mingquan Ding; Yurong Jiang; Junkang Rong (Molecular Genetics and Genomics, 2024)

Amplification of warming-wetting in high mountains and associated mechanisms during the 21st century in Xinjiang, Central Asia - Rong Chen; Keqin Duan; Peihong Shi; Wei Shang; Junhua Yang; Jinping He; Yali Meng; Mingyu Dou; Liang Li (Climatic Change, 2024)

Noradrenergic Projections from the Locus Coeruleus to the Medial Prefrontal Cortex Enhances Stress Coping Behavior in Mice Following Long-Term Intermittent Fasting - Zheng Zhao; Jun-Liang Chen; Han Zhan; Chang-Rong Fang; Li-Bo Hua; Hao-Yuan Deng; Zongqin Xiang; Ying Yang; Lang Huang; Yong U. Liu (NeuroMolecular Medicine, 2024)

White matter lesions contribute to motor and non-motor disorders in Parkinson’s disease: a critical review - Yue-Qi Jiang; Qiu-Zhu Chen; Yang Yang; Cai-Xia Zang; Jing-Wei Ma; Jin-Rong Wang; Yi-Rong Dong; Ning Zhou; Xing Yang; Fang-Fang Li; Xiu-Qi Bao; Dan Zhang (GeroScience, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Synergic treatment of domestic wastewater and food waste in an anaerobic membrane bioreactor demo plant: Process performance, energy consumption, and greenhouse gas emissions - Zhen Lei; Jiale Zheng; Jiale Liu; Qian Li; Jingjing Xue; Yuan Yang; Zhe Kong; Yu-You Li; Rong Chen (Water Research, 2024)

Promotion of aromatic amino acids of extracellular polymeric substance targeted transformation via sulfite mediated iron redox cycling in sludge solid-liquid separation - Jiahao Lai; Huan Liu; Zhen Yang; Rong Deng; Yun Xiong; Yafei Li; Min Song (Water Research, 2024)

A novel cleaner production for ferromagnetic materials from red mud: Process design, thermodynamic study and environment assessment - Yadong Wu; Fangqi Li; Wei Liu; Chaosen Yang; Rong Liu; Hongsheng Huang (Process Safety and Environmental Protection, 2024)

The effect of mixed microbial agents on tobacco black shank disease - Fang Liang; Chai Yunxia; Li Yuanyuan; Geng Shaowu; Bu Yunhong; Hu Yang; Ai Kebiao; Shi Jianfei; Duan Jiyou; Yang Maosong; Zhu Rong (Physiological and Molecular Plant Pathology, 2024)

Identification and performance of endophytic actinobacteria Ahn65 with functions of growth promotion and disease resistance for rice - Hua Yang; Zhan Hu; Rong Xiao; Zhu-dong Liu; Min Zhang; Yi-Lu Li; Shan-dong Wu; Zu-jiao Fu (Physiological and Molecular Plant Pathology, 2024)

Enhanced photocatalytic hydrogen evolution via yolk–heteroshell TiO2@TiO2/SiO2 nanoreactor with confined Pt nanoparticles - Haimei Liu; Min Shi; Rong Yang; Ye Wang; Haiyan li; Qiying Su; Tao Wang; Sheng Wang (Chemical Engineering Journal, 2024)

Preparation of super toughened flame-retardant polylactic acid with an in situ hyperbranched structure by reactive blending with a phosphorus-containing copolyester and hexamethylene glycidyl cyclotriphosphazene - Guozhang Gu; Huaiyang Cai; Yutao Wang; Chen Tang; Guoxiang Zou; Jinchun Li; Rong Yang (Chemical Engineering Journal, 2024)

Combined utilization of slag, fly ash, and polyacrylamide for sustainable saline soil improvement: a win-win strategy - Yang Zhao; Zheng Lu; Rong Zhang; Jie Liu; Changtao Hu; Abdollah Tabaroei; Jian Li; Tingzhou Yan; Hailin Yao (Bulletin of Engineering Geology and the Environment, 2024)

Early detection of fungal infection in citrus using biospeckle imaging - Si Yang; Chenxi Li; Xinyu Li; Jingying Jiang; Yansong Zhao; Xiaoli Wang; Wenliang Chen; Rong Liu; Kexin Xu (Computers and Electronics in Agriculture, 2024)

Recent research and development of individual precision cooling systems for dairy cows – A review - Wenqi Zhang; Ruimin Yang; Christopher Y. Choi; Li Rong; Guoqiang Zhang; Kaiying Wang; Xiaoshuai Wang (Computers and Electronics in Agriculture, 2024)

Organic fertilizer substitution benefits microbial richness and wheat yield under warming - Zheng-Rong Kan; Yinan Xu; Ahmad Latif Virk; Mengting Liu; Xinyu Pei; Yanling Li; Haishui Yang; Changqing Chen (Science of The Total Environment, 2024)

Ru0.7Cu0.3/W18O49 Schottky junction for visible-light-driven hydrogen generation from ammonia borane hydrolysis - Shu-Bin Li; Wei-Yang Long; Chuan-Qi Li; Yan-Xin Duan; Rong-Chao Cui; Zhong-Yi Liu; Xin-Zheng Yue (Fuel, 2024)

Gum arabic coating alleviates chilling injury of cold-stored peach by regulating reactive oxygen species, phenolic, and sugar metabolism - Zengyu Gan; Yupei Zhang; Ziteng Jin; Yongjie Wang; Jiali Li; Caining Yang; Qing Cao; Jinyin Chen; Zhenbang Rong; Xuming Lu; Suqin Guo (Food Chemistry, 2024)

The impacts of cold plasma on the taste and odor formation of dried silver carp products - Yueying Zhai; Aonan Luan; Zhimeng Yang; Zhixing Rong; Yongle Liu; Faxiang Wang; Xianghong Li (Food Chemistry, 2024)

Effect of whole-grain Tartary buckwheat fermentation with Monascus purpureus on the metabolic syndrome and intestinal flora in mice - Xin Yang; Rong Ren; Xiaoqin Lang; Xuanchen Li; Likang Qin; Haiying Zeng (Food Bioscience, 2024)

Development of easy-to-swallow and lipid-enhanced 3D printed surimi based on high internal phase emulsions - Wei Liang; Yuhang Wang; Chuan Li; Pengkai Wang; Jianhua Rong; Ru Liu; Shanbai Xiong; Yang Hu (Food Hydrocolloids, 2024)

Effects of co-assembly of gliadin and carboxymethyl cellulose on the high internal phase pickering emulsions: Rheology properties, 3D printing performance and oil-soluble nutrient delivery - Duo Zhang; Yongkang Yang; Rixin Li; Xing Rong; Wenli Zhang; Miao Zhang; Bin Li; Xuan Zhang (Food Hydrocolloids, 2024)

Constructing ultralow-loading Cu single atoms/Fe2O3 particles on Nb2C MXenes for efficient utilization of atomic H to boost electrochemical debromination - Fangxian Wang; Junwei Yang; Shihao Li; Junwen Liang; Yuwei Wang; Rong Du; Bo Zhou; Qiong Liu; Changping Li (Chemical Engineering Journal, 2024)

Influenza A Virus PB1-F2 Induces Affective Disorder by Interfering Synaptic Plasticity in Hippocampal Dentate Gyrus - Saiying Wang; Haijun Zhang; Rui Liu; Peijun Han; Qi Yang; Caiyan Cheng; Yue Chen; Zheng Rong; Chang Su; Fei Li; Gaofei Wei; Minggao Zhao; et al. (Molecular Neurobiology, 2024)

Effects of Humic Acid-Copper Interactions on Growth, Nutrient Absorption, and Photosynthetic Performance of Citrus sinensis Seedlings in Sand Culture - Wei-Tao Huang; Qian Shen; Hui Yang; Xu-Feng Chen; Wei-Lin Huang; Han-Xue Wu; Ning-Wei Lai; Lin-Tong Yang; Zeng-Rong Huang; Li-Song Chen (Journal of Plant Growth Regulation, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Role of NF-κB signaling pathway in H2O2-induced oxidative stress of hiPSCs - Jian Qin; Jie Yang; Jun Li; Dipeng Zhao; Jie An; Zhuhui Zhai; Hejie Wang; Junling Li; Minmin Dou; Rong Du (In Vitro Cellular & Developmental Biology - Animal, 2024)

Dual colorimetric platforms for direct detection of glyphosate based on Os-Rh nanozyme with peroxidase-like activity - Yingying Zhong; Junsong Yang; Wanying Wu; Haoyang Chen; Shuwei Li; Ziying Zhang; Shicheng Rong; Hongwu Wang (Analytica Chimica Acta, 2024)

Glutamine deprivation in glioblastoma stem cells triggers autophagic SIRT3 degradation to epigenetically restrict CD133 expression and stemness - Zhengcao Xing; Xianguo Jiang; Yalan Chen; Tiange Wang; Xiaohe Li; Xiangyun Wei; Qiuju Fan; Jie Yang; Hongmei Wu; Jinke Cheng; Rong Cai (Apoptosis, 2024)

Metabolic Heterogeneity and Potential Immunotherapeutic Responses Revealed by Single-Cell Transcriptomics of Breast Cancer - Shicong Tang; Qing Wang; Ke Sun; Ying Song; Rui Liu; Xin Tan; Huimeng Li; Yafeng Lv; Fuying Yang; Jiawen Zhao; Sijia Li; Pingping Bi; et al. (Apoptosis, 2024)

CXCR3 participates in asymmetric division of mouse oocytes by modulating actin dynamics - Wei-jian Li; Rong-yang Li; Da-yu Wang; Ming Shen; Hong-lin Liu (Theriogenology, 2024)

Preliminary assessments of carbon release driven by Late Pleistocene Arctic ice sheets - Liming Ye; Xiaoguo Yu; Yeping Bian; Weijia Fan; Zhongqiang Ji; Sai Song; Ziyin Wu; Qian Ge; Dong Xu; Weiyan Zhang; Haiyan Jin; Xiaohu Li; et al. (Quaternary Science Reviews, 2024)

A pooled mycoviral resource in a strain of Rhizoctonia solani are regulators of fungal virulence - Ya Rong Wang; Jia En Su; Zhi Juan Yang; Jie Zhong; Xiao Gang Li; Yi Chen; Jun Zi Zhu (Pesticide Biochemistry and Physiology, 2024)

Genetic variation in a heat shock transcription factor modulates cold tolerance in maize - Lei Gao; Lingling Pan; Yiting Shi; Rong Zeng; Minze Li; Zhuoyang Li; Xuan Zhang; Xiaoming Zhao; Xinru Gong; Wei Huang; Xiaohong Yang; Jinsheng Lai; et al. (Molecular Plant, 2024)

Bamboo vinegar regulates the phytoremediation efficiency of Perilla frutescens (L.) Britt. by reducing membrane lipid damage and increasing cadmium retention - Zhenguo Li; Xingyu Hao; Tianlian He; Ying Chen; Mingwei Yang; Cheng Rong; Chengzhen Gu; Qingtie Xiao; Ruiyu Lin; Xinyu Zheng (Journal of Hazardous Materials, 2024)

Effects of straw biochar on microbial-derived carbon: A global meta-analysis - Jinkang Yang; Li Li; Yinan Xu; Yalin Yu; Ahmad Latif Virk; Feng-Min Li; Haishui Yang; Zheng-Rong Kan (Journal of Environmental Management, 2024)

Ca2+-nano starch-lutein endowed 3D printed surimi with antioxidation and mutual reinforcing transmembrane transport mechanisms via hepg2 and caco-2 cells model - Gaoshang Li; Rong Shi; Junqi Zhan; Yiduo Wu; Yue Wan; Qian Yao; Yaqin Hu; Chunhua Wu; Wenge Yang; Wubo Wan (Food Research International, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

Gypsum ridges as conduits for deep methane emission in an evaporite basin– Insights into the origin of atmospheric methane on Mars - Yiliang Li; Zikang Li; Xiaorong Qin; Binlong Ye; Ziyu Niu; Anouk Ehreiser; Wenhua Zhang; Yang Pan; Liping Qin; Rong Shu; Jianxi Zhu; Yigang Xu; et al. (Earth and Planetary Science Letters, 2024)

Two-stage exhumation, uplift, and basinward propagation of the Tian Shan during the late Cenozoic - Yutong Jiang; Honghua Lu; Rong Yang; Lichen Pang; Ruohong Jiao; Ying Wang; Jianzhang Pang; Youli Li (Earth-Science Reviews, 2024)

Ti2TaC2: A novel out-of-plane ordered MXene towards flexible and cytocompatible supercapacitors - Yunfeng Guan; Lixian Jiang; Rong Zhao; Xuanke Li; Hui Zhu; Qin Zhang; Zhijun Dong; Nianjun Yang; Ye Cong (Chemical Engineering Journal, 2024)

Synergistic optimization of the water state and transport pathway in hydrogels via pullulan and directional Freezing-Assisted salting out for efficient evaporation - Huanwei Shen; Xiayue Yang; Wenhao Li; Zhihua Sha; Hongmei Luo; Zixuan Li; Sihan Dong; Wei Cui; Rong Ran (Chemical Engineering Journal, 2024)

TBC1D1 is an energy-responsive polarization regulator of macrophages via governing ROS production in obesity - Qi Wang; Ping Rong; Wen Zhang; Xinyu Yang; Liang Chen; Ye Cao; Minjun Liu; Weikuan Feng; Qian Ouyang; Qiaoli Chen; Hailong Li; Hui Liang; et al. (Science China Life Sciences, 2024)

Argon non-thermal plasma treatment promotes the development of rice (Oryza sativa L.) in saline alkali environments - Kai Liu; Yan-Jiang Feng; Jun-Xiang Guo; Gui-Ling Wang; Li-Li Shan; Shi-Wei Gao; Qing Liu; Hu-Nan Sun; Xi-Yu Li; Xing-Rong Sun; Jing-Yang Bian; Taeho Kwon (Protoplasma, 2024)

Evolution and deposition patterns of turbidity currents under complex vegetation canopies - Jiayi Li; Yantun Song; Chongfa Cai; Liwen Qiu; Rong Hao; Changhua Zhan; Qiong Yang (Journal of Hydrology, 2024)

Digestion and absorption characteristics of iron-chelating silver carp scale collagen peptide and insights into their chelation mechanism - Qiannan Zhao; Wei Liang; Zhe Xiong; Chuan Li; Lu Zhang; Jianhua Rong; Shanbai Xiong; Ru Liu; Juan You; Tao Yin; Yang Hu (Food Research International, 2024)

Adenylate kinase phosphate energy shuttle underlies energetic communication in flagellar axonemes - Huan Wu; Yanman Zhang; Yuqian Li; Shuya Sun; Jintao Zhang; Qingsong Xie; Yue Dong; Shushu Zhou; Xuan Sha; Kuokuo Li; Jinyi Chen; Xin Zhang; et al. (Science China Life Sciences, 2024)

Associations of Plasma Lipidomic Profiles with Uric Acid and Hyperuricemia Risk in Middle-Aged and Elderly Chinese - Wanhui Kang; Xinming Xu; Xiaowei Yang; Qingqing Wu; Shuning Li; Keran Gao; Rong Zeng; Liang Sun; Xu Lin (Phenomics, 2024)
Little is known about the links of disturbed lipid metabolism with hyperuricemia (HUA). We aimed to investigate the associations of lipidomic profiles with uric acid (UA)/HUA and their modifying factors in middle-aged and elderly Chinese. A total of 350 lipids were quantified in 2247 community-based Chinese aged 50–70 years by high-coverage targeted lipidomics. HUA was defined by plasma UA > 420 μmol/L in men or > 360 μmol/L in women. The prevalence of HUA in this population was 10.4%. After multivariable adjustment including BMI and lifestyle, 123 lipids were significantly associated with UA, predominantly glycerolipids (GLs) and glycerophospholipids (GPs). Specifically, diacylglycerol [DAG (16:0/22:5), DAG (16:0/22:6), DAG (18:1/20:5), DAG (18:1/22:6)], phosphatidylcholine [PC (16:0/20:5)), and triacylglycerol (TAG (53:0)] were the most significant lipid signatures positively associated with HUA risk, while lysophosphatidylcholine (LPC (20:2)) was inversely associated with HUA risk ( p < 0.05). Network analysis also showed a positive association between TAGs/PCs/DAGs contained module and HUA risk ( p < 0.01). Notably, HUA-related lipids were associated with de novo lipogenesis fatty acids, especially 16:1n-7 (Spearman correlation coefficients = 0.32–0.41, p < 0.001). Reduced rank regression showed that increased aquatic products intake was correlated to elevated HUA risk and HUA-associated lipids; while high dairy consumption was correlated with low level of HUA-associated lipids (|factor loadings| ≥ 0.2). Moreover, mediation analyses suggested that the lipid-HUA associations were partially mediated by retinol-binding protein 4 (RBP4, mediation proportion 5–14%), an adipokine linked with dyslipidemia and insulin resistance. In conclusion, disturbed specific metabolisms of GLs and GPs were associated with high prevalent HUA, partially mediated by RBP4 and/or influenced by certain dietary factors.

Identification of the Galactinol Synthase (GolS) Family in Medicago truncatula and Expression Analysis Under Abiotic Stress and Phytohormone Treatment - Hua Li; Ying Di Gao; Li Qing Kang; Hong Yang Yu; Li Ming Zeng; Yi Hua Wang; Rong Rong Chen; Jian Bo Song (Journal of Plant Growth Regulation, 2024)

Microneedle electrochemical sensor based on disposable stainless-steel wire for real-time analysis of indole-3-acetic acid and salicylic acid in tomato leaves infected by Pst DC3000 in situ - Lingjuan Tang; Daodong Li; Wei Liu; Yihui Tang; Rongcheng Zhang; Yiran Tian; Rong Tan; Xiaolong Yang; Lijun Sun (Analytica Chimica Acta, 2024)

Deubiquitinating enzyme OTUD4 stabilizes RBM47 to induce ATF3 transcription: a novel mechanism underlying the restrained malignant properties of ccRCC cells - Ziyao Li; Ye Tian; Huafeng Zong; Xuelei Wang; Dongyang Li; Adili Keranmu; Shiyong Xin; Bowen Ye; Rong Bai; Weihua Chen; Guosheng Yang; Lin Ye; et al. (Apoptosis, 2024)

Characteristics and degradation mechanisms of polychlorinated naphthalenes in surface soil in Yangtze River Delta, China - Zherui Zhang; Guohua Zhu; Yahui Liu; Xin Zhou; Bingcheng Lin; Ziyuan Qi; Shanshan Zhang; Yueyao Yang; Xin Li; Rong Jin; Minghui Zheng (Chemosphere, 2024)

Assessment of spray nozzles on water distribution on cow’s surface and efficiency of water utilization by CFD - Ruimin Yang; Christopher Y. Choi; Li Rong; Guoqiang Zhang; Xiaoshuai Wang (Computers and Electronics in Agriculture, 2024)

Genomic analysis of Clostridium perfringens type D isolates from goat farms - Hang Feng; Ke Wu; Yuan Yuan; Mingjin Fang; Juan Wang; Ruichao Li; Rong Zhang; Xinglong Wang; Dongyang Ye; Zengqi Yang (Veterinary Microbiology, 2024)

Timing and Kinematics of late Cenozoic Strike-slip Faults in the Western Tibetan Plateau: New Constraints from Provenance Analysis and Detrital Thermochronology - Xiaochun Wei; Hanlin Chen; Rong Yang; Ping Wang; Shanying Li; Xuhua Shi; Jin Ge (Tectonophysics, 2024)

Preharvest spraying with L-Phenylalanine effectively delayed the degradation of chlorophyll in postharvest broccoli - Xiwang Wang; Deyun Lou; Li Li; Rong Li; Wenyi Xu; Xiaojing Wang; Yongcai Li; Yang Bi (Postharvest Biology and Technology, 2024)

An approach based on a combination of toxicological experiments and in silico predictions to investigate the adverse outcome pathway (AOP) of paraquat neuro-immunotoxicity - Chunhui Zhang; Ge Shi; Qi Meng; Rong Hu; Yang Li; Guiling Hu; Kaidong Wang; Min Huang (Journal of Hazardous Materials, 2024)

Divergent impacts of fertilization regimes on below-ground prokaryotic and eukaryotic communities in the Tibetan Plateau - Shuo Sun; Chen Liu; Yun Zhang; Yang Yue; Shiqi Sun; Yang Bai; Pengfei Zhang; Mohammadhossein Ravanbakhsh; Francisco Dini-Andreote; Rong Li; Zhenhua Zhang; Alexandre Jousset; et al. (Journal of Environmental Management, 2024)

Catalytic hydrotreatment of fast pyrolysis liquids from Pine wood using Ru-based catalysts supported on nitrogen-doped carbon materials - Yunhui Xia; Nan Xi; Xinyang Yu; Maohua Luo; Shi Chen; Qinglian Wang; Yixiong Lin; Rong Wang; Hao Li; Jun Yue; Chen Yang; Wang Yin; et al. (Fuel, 2024)

Formation mechanism, environmental sensitivity and functional characteristics of succinylated ovalbumin/ε-polylysine electrostatic complexes: The roles of succinylation modification and ε-polylysine combination - Ru-yi Zhang; Hui-min Zhang; Tian-zhu Guan; Zhi-rong Wang; Hua-xiang Li; Lei Yuan; Yan-jun Yang; Sheng-qi Rao (Food Chemistry, 2024)

Phyllanthus emblica Linn: A comprehensive review of botany, traditional uses, phytonutrients, health benefits, quality markers, and applications - Qin-Ge Ma; Lei Wang; Rong-Hua Liu; Jin-Bin Yuan; Hui Xiao; Zhang-Yang Shen; Jia-Xin Li; Jia-Zeng Guo; Lan Cao; Hui-Lian Huang; Rong-Rui Wei (Food Chemistry, 2024)

The influence of vegetation restoration on soil quality in abandoned farmlands in the Yuanjiang dry-hot valley - Guanghai Wang; Yifan Dong; Li Rong; Wantao Yang; Xingwu Duan (CATENA, 2024)

Functional comparison of Rab3aa and Rab3ab in grass carp (Ctenopharyngodon idella) immune response and GCRV replication - Lifei Luo; Lv Xiong; Cheng Yang; Libo He; Lanjie Liao; Yongming Li; Zuoyan Zhu; Yaping Wang; Rong Huang (Aquaculture, 2024)

Capnesterones A and B, new steroids isolated from the soft coral Capnella imbricata - Ting-Yu Cheng; Chia-Jung Yang; Po-Jen Chen; Yu-Li Chen; Bo-Rong Peng; Te-An Kung; Zhi-Hong Wen; Kuei-Hung Lai; Hsu-Ming Chung (Phytochemistry Letters, 2024)

A Pennsylvanian rugose coral assemblage from eastern Junggar Basin, Northwest China - Sun-Rong Yang; Le Yao; Zhang-Shuai Hou; Xun-Yan Ye; Ying Li; Xing Huang; Shu-Zhong Shen; Xiang-Dong Wang (Palaeoworld, 2024)

OsPRMT6a-mediated arginine methylation of OsJAZ1 regulates jasmonate signaling and spikelet development in rice - Kun Dong; Fuqing Wu; Siqi Cheng; Shuai Li; Feng Zhang; Xinxin Xing; Xin Jin; Sheng Luo; Miao Feng; Rong Miao; Yanqi Chang; Shuang Zhang; et al. (Molecular Plant, 2024)

Multistage dolomitization influenced by the Emeishan large igneous province: Petrographical and geochemical evidence - Yang Li; Xiyan Yang; Xinzhi Wang; Cunhui Fan; Xiangyu Fan; Yu Zhang; Rong Yang; Yue Li; Zisang Huang; Fei Huo (Marine and Petroleum Geology, 2024)

Long-term residue returning increased subsoil carbon quality in a rice-wheat cropping system - Yinan Xu; Yalin Yu; Jing Sheng; Yuekai Wang; Haishui Yang; Feng-Min Li; Shiping Liu; Zheng-Rong Kan (Journal of Environmental Management, 2024)

ZnO nanorod coatings attenuate antibiotic resistance genes (ARGs) on their surface biofilms in estuarine environment - Xing-pan Guo; Rong-rong Sha; Yu-cen Wang; Jia Yan; Bo Peng; Zuo-shun Niu; Wen-liang Liu; Xin Li; Yi Yang (Journal of Environmental Chemical Engineering, 2024)

High mineralization efficiency of chlorobenzene oxidation using a metal-interaction strengthening MnCoOx catalyst derived from ZIF-67 - Shuangshuang Fu; Dongjie Yan; Dan Tao; Ning Yang; Kaixian Liu; Yifan Rong; Lu Li; Chi He (Fuel, 2024)

Determination of marker residues of quinoxaline-1,4-di-N-oxides and its prototype identification by liquid chromatography tandem mass spectrometry - Lu Li; Rong Liu; Longyun Liu; Zeyu Guo; Tong Zhou; Yuxi Yang; Huiping Yang; Limin He (Food Chemistry, 2024)

Metabolome and transcriptome reveal high abundance of bioactive substances in albino jujube fruit as potential function food - Yang Wang; Yong Huang; Panhui Song; Xuemei Peng; Xinyu Li; Rong Su; Hui Zhang; Lijin Lin; Hui Xia; Qunxian Deng (Food Bioscience, 2024)

Prospective findings from the Dongfeng-Tongji cohort: Exposure to various metals, the expression of microRNA-4286, and the incidence of acute coronary syndrome - Miaoyan Shen; Xuedan Xu; Wending Li; Xi Wang; Rong Peng; Xuezhen Liu; Qiuhong Wang; Xiaomin You; Pinpin Long; Hao Wang; Rundong Niu; Yu Yin; et al. (Environmental Research, 2024)

Effects of Hericium erinaceus polysaccharide in porcine IPEC-J2 intestinal epithelial cells against apoptosis induced by oxidative stress - Jian Li; Jia-rong Mo; Shi-yu Hu; Xin Dong; Jia-wei Li; Li-yu Yang; Yi-jian Wu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Boosting persulfate activation through efficient π → π* transition activated by Cu ion anchored porphyrin-based metal–organic framework - Wen-Qiang Li; Oleksandr Savateev; Yuan-Ming Li; Jian-Kang Zheng; Yi-Xuan Wang; Nannan Hou; Xiao-Cheng Liu; Rong-Rong Ding; Xiao-Guo Zhou; Yang Wang; Xian-Yang Shi; Yang Mu (Chemical Engineering Journal, 2024)

Polyoxovanadate Li7[V15O36(CO3)] and its derivative γ-LiV2O5 as superior performance cathode materials for aqueous zinc-ion batteries - Haoran Xiao; Xin Du; Rong Li; Hao Jin; Lingling Xie; Qing Han; Xuejing Qiu; Xinli Yang; Limin Zhu; Xiaoyu Cao (Chemical Engineering Journal, 2024)

Chemical constituents from Albatrellus confluence and their chemotaxonomic significance - Qing-Fang Wang; Jing-Rong Ou-Yang; Ting-Ting Guo; Ming-Ming Li; Hong-Ping He (Biochemical Systematics and Ecology, 2024)

Chemical constituents of the deep-sea-derived fungus Trichoderma simmonsii ZEN3 and their chemotaxonomic significance - Li-Fang Liu; Yuan Wang; Rong Chao; Lin Xu; Zheng-Biao Zou; Kai Zhang; Ming-Min Xie; Xian-Qiang Chen; Cheng-Hai Gao; Xian-Wen Yang (Biochemical Systematics and Ecology, 2024)

Chemical constituents and chemotaxonomic research of the deep-sea-derived fungus Aspergillus japonicus W6 - Tong Yu; Rong Chao; Zheng-Biao Zou; Jia-Xin Duan; Kai Zhang; You Li; Ming-Min Xie; Yong Zhang; Ying-Ni Pan; Xian-Wen Yang (Biochemical Systematics and Ecology, 2024)

Expert Consensus on Big Data Collection of Skin and Appendage Disease Phenotypes in Chinese - Shuang Zhao; Zhongling Luo; Ying Wang; Xinghua Gao; Juan Tao; Yong Cui; Aijun Chen; Daxing Cai; Yan Ding; Heng Gu; Jianying Gu; Chao Ji; et al. (Phenomics, 2024)

A Novel FD3 Framework for Carbon Emissions Prediction - Houtian He; Tongyan Liu; Qianqian Li; Jiaru Yang; Rong-Long Wang; Shangce Gao (Environmental Modeling & Assessment, 2024)

Experimental and Numerical Study of Suspended Inter-Array Cable Configurations for Floating Offshore Wind Farm - Di-Rong Li; Yu-Shiou Su; Ray-Yeng Yang (Journal of Marine Science and Engineering, 2024)
The present study evaluates the feasibility of using a fully suspended inter-array cable system for an offshore wind farm. It includes both numerical simulations and a scaled-down experiment, conducted at a 1:49 scale, to validate the numerical results. To achieve the goal, a 15 MW floating offshore wind turbine (FOWT) and a floating offshore substation (FOSS) are involved to simulate the wind farm array. This study incorporates the 50-year return period conditions of the Taiwan Hsinchu offshore area, which has a water depth of about 100 m, to validate the specifications related to the platform motion and mooring line tension. Additionally, an analysis of the tension, curvature, and fatigue damage of the dynamic cable system is discussed in this research. Because a fully suspended cable is a relatively new concept and may be more frequently considered in a deeper water depth area, numerical simulation software Orcina Orcaflex 11.4 has been chosen to conduct the fully coupled simulation, determining whether the fully suspended cable system could effectively withstand the challenges posed by extreme sea conditions. This is due to the reason that a fully suspended cable would occupy a larger space in the ocean, which may pose a risk by influencing the navigation of the vessels. Therefore, the cable laying depth under normal sea states is also discussed to evaluate the influence over vessel navigation. This study also collects the long-term environmental data from the Central Weather Bureau, Taiwan, to calculate the accumulative cable fatigue damage under different sea states. To integrate the results, this research applies fitness parameters to evaluate the feasibility of each cable configuration. Covering the cable performance under extreme sea states and regular operating sea states offers valuable insights for applications in ocean engineering.

The potential use of Zymomonas mobilis for the food industry - Lu Liu; Jian-Ting Li; Sheng-Hao Li; Lin-Pei Liu; Bo Wu; Yan-Wei Wang; Shi-hui Yang; Cheng-Han Chen; Fu-Rong Tan; Ming-Xiong He (Critical Reviews in Food Science and Nutrition, 2024)

CYTOR-NFAT1 feedback loop regulates epithelial-mesenchymal transition of retinal pigment epithelial cells - Rong Zhang; Lin Wang; Yang Li; Yan Liu; Kui Dong; Yajing Pei; Junmei Zhao; Gang Liu; Jing Li; Xiaodan Zhang; Tong Cui; Yan Gao; et al. (Human Cell, 2024)

Advances in understanding bioaerosol release characteristics and potential hazards during aerobic composting - Sai Yang; Yanan Yin; Wenrong Zhang; Haichao Li; Xiaochang Wang; Rong Chen (Science of The Total Environment, 2024)

Neural network establishes co-occurrence links between transformation products of the contaminant and the soil microbiome - Yuhui Xiang; Yansong Yu; Jiahui Wang; Weiwei Li; Yu Rong; Haibo Ling; Zhongbing Chen; Yiguang Qian; Xiaole Han; Jie Sun; Yuyi Yang; Liang Chen; et al. (Science of The Total Environment, 2024)

Impact of atmospheric dryness on solar-induced chlorophyll fluorescence: Tower-based observations at a temperate forest - Koong Yi; Rong Li; Todd M. Scanlon; Manuel T. Lerdau; Joseph A. Berry; Xi Yang (Remote Sensing of Environment, 2024)

Massive early Middle Pleistocene cheetah from eastern Asia shed light onto the evolution of Acinonyx in Eurasia - Qigao Jiangzuo; Yaming Wang; Joan Madurell-Malapeira; Saverio Bartolini Lucenti; Shijie Li; Shiqi Wang; Zhaoyu Li; Rong Yang; Yi Jia; Lu Zhang; Shanqin Chen; Changzhu Jin; et al. (Quaternary Science Reviews, 2024)

Experimental and numerical study on the integration of a built-in wave energy converter(BIWEC) and floating platform - Wenbin Lai; Jialong Li; Sizhang Rong; Hongkun Yang; Xiongbo Zheng (Ocean Engineering, 2024)

Biodegradation of various grades of polyethylene microplastics by Tenebrio molitor and Tenebrio obscurus larvae: Effects on their physiology - Meng-Qi Ding; Jie Ding; Zhi-Rong Zhang; Mei-Xi Li; Chen-Hao Cui; Ji-Wei Pang; De-Feng Xing; Nan-Qi Ren; Wei-Min Wu; Shan-Shan Yang (Journal of Environmental Management, 2024)

Radio frequency heating induced 3D printed white croaker (Argyrosomus argentatus) surimi gelation: Effectiveness and gel quality evaluation - Yaxing Yang; Feifan Cao; Rong Han; Feng Li; Hu Shi; Fanbin Kong; Yang Jiao (Innovative Food Science & Emerging Technologies, 2024)

Modifying duck myofibrillar proteins using sodium bicarbonate under cold plasma treatment: Impact on the conformation, emulsification, and rheological properties - Shengqi Jiang; Chunjie Yang; Rong Bai; Ziwei Li; Linlu Zhang; Ya Chen; Xiang Ye; Siying Wang; Hao Jiang; Wu Ding (Food Hydrocolloids, 2024)

Straw management adopted by large farms sustains grain yield but mitigates greenhouse gas emissions - Zhenzhen Li; Yong Lin; Zheng-Rong Kan; Sana ur Rehman; Atta Mohi Ud Din; Feng-Min Li; Shixiang Zhang; Ping Wu; Yingfu Ding; Chensheng Xu; Congying Rao; Huaxin Dai; et al. (Field Crops Research, 2024)

Unravelling the safety improving and failure mechanisms of a 56.5 Ah high-energy–density Li-ion cell containing solid-state electrolyte - Wei Zhang; Xiaopeng Qi; Min Liu; Bingxue Liu; Yuansen Hu; Jing Ye; Rennian Wang; Bin Li; Changhong Wang; Qian Huang; Bing Yu; Rong Yang; et al. (Chemical Engineering Journal, 2024)

Ginsenoside Rg1 Alleviates Sepsis-Induced Acute Lung Injury by Reducing FBXO3 Stability in an m6A-Dependent Manner to Activate PGC-1α/Nrf2 Signaling Pathway - Rong Liu; Qiang Wang; Yao Li; Ruixue Wan; Ping Yang; Dexing Yang; Jiefu Tang; Jiafei Lu (The AAPS Journal, 2024)

Advances in ionogels for proton-exchange membranes - Yilin Zhou; Bei Wang; Zhiwei Ling; Qingting Liu; Xudong Fu; Yanhua Zhang; Rong Zhang; Shengfei Hu; Feng Zhao; Xiao Li; Xujin Bao; Jun Yang (Science of The Total Environment, 2024)

A specific module of ESCRT regulates STING activity termination by controlling STING degradation - Yuan Zhao; Chenxuan Zhou; Wenmin Tian; Yang Chen; Chongchong Zhao; Yan Li; Shixuan Wang; Yueguang Rong (Science Bulletin, 2024)

The double-edged effects of La2O3 and CeO2 on the performance of high-rate anaerobic sludge bed reactors and microbial mechanisms - Kai Su; Lin-xiao Li; Zhuo Zeng; Xue Yang; Tao Lei; Han Zhang; Qin Wang; Rong Cao (Process Safety and Environmental Protection, 2024)

Boron-mediated amelioration of copper toxicity in Citrus sinensis seedlings involved reduced concentrations of copper in leaves and roots and their cell walls rather than increased copper fractions in their cell walls - Huan-Huan Chen; Zhi-Chao Zheng; Dan Hua; Xu-Feng Chen; Zeng-Rong Huang; Jiuxin Guo; Lin-Tong Yang; Li-Song Chen (Journal of Hazardous Materials, 2024)

An integrated calibration strategy for the development and validation of an LC-MS/MS method for accurate quantification of egg allergens (Gal d 1–6) in foods - Shupeng Yang; Jingjing Chen; Mohamed F. Abdallah; Haopeng Lin; Peijie Yang; Jianxun Li; Rong Zhang; Qianqian Li; Peng Lu; Shuyan Liu; Yi Li (Food Chemistry, 2024)

Resistance of biological magnetic ion exchange resin to norfloxacin on the advanced treatment of wastewater - Liqin Han; Cong Shan; Chendong Shuang; Shanshan Xu; Qing Zhou; Rong Ji; Aimin Li; Yang Pan (Chemical Engineering Journal, 2024)

Fine mapping and candidate gene analysis of qSRC3 controlling the silk color in maize (Zea mays L.) - Xueying Wang; Yang Zhou; Chong You; Jinchang Yang; Zhengjie Chen; Dengguo Tang; Jixing Ni; Peng Li; Le Wang; Kaili Zhu; Wujiao Deng; Haimei Wu; et al. (Theoretical and Applied Genetics, 2024)

Inflammatory cell death PANoptosis is induced by the anti-cancer curaxin CBL0137 via eliciting the assembly of ZBP1-associated PANoptosome - Ya-Ping Li; Zhi-Ya Zhou; Liang Yan; Yi-Ping You; Hua-Yu Ke; Tao Yuan; Hai-Yan Yang; Rong Xu; Li-Hui Xu; Dong-Yun Ouyang; Qing-Bing Zha; Xian-Hui He (Inflammation Research, 2024)

Three-dimensional DNA biomimetic networks (B-3D Net)-based ratiometric fluorescence platform for cancer-related gene biosensing - Chao Yao; Guiqun Zhang; Hongling Tao; Yulong Li; Rong Hu; Yunhui Yang (Analytica Chimica Acta, 2024)

Three new diterpenoids isolated from Euphorbia nematocypha Hand.-Mazz and their anti-fungal activity - Rong-Shuai Li; Zhi-Chang Xu; Ding-Mei Qin; Jia-Bi Huang; Meng-Ru Wang; Xue-Rong Zhao; Quan-Yu Yang; Wei-Lie Xiao; Rui-Rui Wang; Xiao-Li Li (Natural Product Research, 2024)

Characterization of multi-copy C3 genes and association analysis of C3.1 polymorphism with GCRV resistance traits in Ctenopharyngodon idella - Jia-yang Huang; Zhao Lv; Bin Li; Yan-rong Ying; Le Yang; Tiao-yi Xiao; Shu-ting Xiong (Aquaculture, 2024)

Phytoremediation and environmental effects of three Amaranthaceae plants in contaminated soil under intercropping systems - Rong Huang; Chen Xing; Yuanru Yang; Wang Yu; Liangbin Zeng; Yanqiong Li; Zhijian Tan; Zhian Li (Science of The Total Environment, 2024)

Tsaokoflavanols A1–J1: Flavanol-fatty alcohol hybrids with HPL inhibitory activity from Amomum tsao-ko - Tian-Rong Yang; Shi-Chao Huang; Yun-Fen Wang; Zai-Xiang Lou; Shao-Xing Dai; Li-Hua Su; Min Xu (Phytochemistry, 2024)

Reservoir characteristics and controlling factors of the middle–high maturity multiple lithofacies reservoirs of the Lianggaoshan Formation shale strata in the northeastern Sichuan basin, China - Xin Wang; Min Wang; Chen Zhao; Xinyi Yang; Yidong Jia; Rong Wu; Tianyi Li; Xinbin Zhao; Yulong Tang (Marine and Petroleum Geology, 2024)

Geomorphic expression of transverse drainages across the Tugerming anticline, southern Tian Shan: Implications for the river-fold interaction in the foreland - Feng Li; Xuhua Shi; Julien Charreau; Xiaogan Cheng; Rong Yang; Hanlin Chen; Jin Ge; Jinghan Wang (Journal of Structural Geology, 2024)

Enhanced detection of acrylamide using a versatile solid-state upconversion sensor through spectral and visual analysis - Yawen Rong; Md Mehedi Hassan; Jizhong Wu; Shuo Chen; Wancheng Yang; Yunhao Li; Jiaji Zhu; Jun Huang; Quansheng Chen (Journal of Hazardous Materials, 2024)

Biochar improves the humification process during pig manure composting: Insights into roles of the bacterial community and metabolic functions - Yanan Yin; Xiaohui Tao; Yifei Du; Mengtong Li; Sai Yang; Wenrong Zhang; Chao Yang; Haichao Li; Xiaochang Wang; Rong Chen (Journal of Environmental Management, 2024)

Biodiversity and core microbiota of key-stone ecological clusters regulate compost maturity during cow-dung-driven composting - Xin Liu; Xiangmin Rong; Pan Jiang; Junyan Yang; Han Li; Yong Yang; Xingxiang Deng; Guixian Xie; Gongwen Luo (Environmental Research, 2024)

Partial organic substitution for synthetic fertilizer improves soil fertility and crop yields while mitigating N2O emissions in wheat-maize rotation system - Gong Wu; Shuo Yang; Chong-sheng Luan; Qi Wu; Lei-li Lin; Xiao-xiao Li; Zhao Che; De-bao Zhou; Zhao-rong Dong; He Song (European Journal of Agronomy, 2024)

3D microprinting of QR-code integrated hydrogel tactile sensor for real-time E-healthcare - Zi-Rong Li; Tian-Run Lv; Zhenxu Yang; Wen-Hai Zhang; Ming-Jie Yin; Ken-Tye Yong; Quan-Fu An (Chemical Engineering Journal, 2024)

Stereoisomerically enhanced polynorbornene-imide dielectric energy storage performance - Hongmei Qin; Man Liu; Shiyu Qin; Shixian Zhang; Xingnan Zhou; Chenjian Li; Yuhao Wei; Dan Chen; Rong Fan; Shan Wang; Quanling Yang; Chuanxi Xiong; et al. (Chemical Engineering Journal, 2024)

New materials of Pliorhinus ringstroemi from the Linxia Basin (Late Miocene, eastern Asia) and their taxonomical and evolutionary implications - Shijie Li; Oscar Sanisidro; Shiqi Wang; Rong Yang; Tao Deng (Journal of Mammalian Evolution, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

A multi-species pest recognition and counting method based on a density map in the greenhouse - Zhiqin Zhang; Jiacheng Rong; Zhongxian Qi; Yan Yang; Xiajun Zheng; Jin Gao; Wei Li; Ting Yuan (Computers and Electronics in Agriculture, 2024)

Performance enhancement of damaged RC structures with viscoelastic dampers: Damage assessment and optimal placement - Zhao-Dong Xu; Yuxuan Tao; Yun Yang; Yao-Rong Dong; Jin Duan; Shihua Li; Hao Wang; Shuai Wang (Soil Dynamics and Earthquake Engineering, 2024)

Optimization of ultrasound-assisted extraction of glycyrrhizic acid and glabridin from Glycyrrhiza glabra L. using response surface methodology and development of a green analytical method - Ye-fei Liang; Qing Wen; Zhen-fei Yang; Cui-qin Li; Fa-rong Li (Sustainable Chemistry and Pharmacy, 2024)

Preparation of potential organic fertilizer rich in γ-polyglutamic acid via microbial fermentation using brewer's spent grain as basic substrate - Fengqing Wang; Yanmei Chen; Jia Zheng; Can Yang; Li Li; Rong Li; Meilin Shi; Zhongxuan Li (Bioresource Technology, 2024)

Relationships between different types of biochar and N2O emissions during composting based on roles of nosZ-carrying denitrifying bacterial communities enriched on compost and biochar particles - Yanan Yin; Mengjin Gu; Wenrong Zhang; Chao Yang; Haichao Li; Xiaochang Wang; Rong Chen (Bioresource Technology, 2024)

Rheumatoid arthritis is a protective factor against Alzheimer’s disease: a bidirectional two-sample Mendelian randomization study - Guo-Shuai Li; Yong-Ze Yang; Guo-Rong Ma; Peng-Fei Li; Qing-Hao Cheng; An-Ren Zhang; Zhuang-Zhuang Zhang; Fu-Kang Zhang; Xin Yang; Hua Fan; Hong-Zhang Guo (Inflammopharmacology, 2024)

Gut microbiome as a key monitoring indicator for reintroductions of captive animals - Guangping Huang; Dunwu Qi; Zhisong Yang; Rong Hou; Wenyu Shi; Fangqing Zhao; Zitian Li; Li Yan; Fuwen Wei (Conservation Biology, 2024)
Reintroduction programs seek to restore degraded populations and reverse biodiversity loss. To examine the hypothesis that gut symbionts could be used as an indicator of reintroduction success, we performed intensive metagenomic monitoring over 10 years to characterize the ecological succession and adaptive evolution of the gut symbionts of captive giant pandas reintroduced to the wild. We collected 63 fecal samples from 3 reintroduced individuals and 22 from 9 wild individuals and used 96 publicly available samples from another 3 captive individuals. By microbial composition analysis, we identified 3 community clusters of the gut microbiome (here termed enterotypes ) with interenterotype succession that was closely related to the reintroduction process. Each of the 3 enterotypes was identified based on significant variation in the levels of 1 of 3 genera: Clostridium , Pseudomonas , and Escherichia . The enterotype of captive pandas was Escherichia . This enterotype was gradually replaced by the Clostridium enterotype during the wild‐training process, which in turn was replaced by the Pseudomonas enterotype that resembled the enterotype of wild pandas, an indicator of conversion to wildness and a successful reintroduction. We also isolated 1 strain of Pseudomonas protegens from the wild enterotype, a previously reported free‐living microbe, and found that its within‐host evolution contributed to host dietary adaptation in the wild. Monitoring gut microbial structure provides a novel, noninvasive tool that can be used as an indicator of successful reintroduction of a captive individual to the wild.

Anthropogenic disturbance driving population decline of a dominant tree in East Asia evergreen broadleaved forests over the last 11,000 years - Sheng‐Yuan Qin; Zheng‐Yu Zuo; Shuang‐Xiu Xu; Jie Liu; Feng‐Mao Yang; Ya‐Huang Luo; Jun‐Wei Ye; Yao Zhao; Jun Rong; Bing Liu; Peng‐Fei Ma; De‐Zhu Li (Conservation Biology, 2024)
Current biodiversity loss is generally considered to have been caused by anthropogenic disturbance, but it is unclear when anthropogenic activities began to affect biodiversity loss. One hypothesis suggests it began with the Industrial Revolution, whereas others propose that anthropogenic disturbance has been associated with biodiversity decline since the early Holocene. To test these hypotheses, we examined the unique vegetation of evergreen broadleaved forests (EBLFs) in East Asia, where humans have affected landscapes since the early Holocene. We adopted a genomic approach to infer the demographic history of a dominant tree ( Litsea elongata ) of EBLFs. We used Holocene temperature and anthropogenic disturbance factors to calculate the correlation between these variables and the historical effective population size of L. elongata with Spearman statistics and integrated the maximum‐entropy niche model to determine the impact of climate change and anthropogenic disturbance on fluctuation in its effective population size. We identified 9 well‐defined geographic clades for the populations of L. elongata . Based on the estimated historical population sizes of these clades, all the populations contracted, indicating persistent population decline over the last 11,000 years. Demographic history of L . elongata and human population change, change in cropland use, and change in irrigated rice area were significantly negatively correlated, whereas climate change in the Holocene was not correlated with demographic history. Our results support the early human impact hypothesis and provide comprehensive evidence that early anthropogenic disturbance may contribute to the current biodiversity crisis in East Asia.

A pair of new chromone enantiomers from Xylaria nigripes - Jing Li; Yue-Ping Jiang; Lan-Qing Li; Hong-Ping Long; Hai-Tao Liu; Rong Yang; Shao Liu; Wen-Xuan Wang; Ji-Kai Liu (Natural Product Research, 2024)

Application and evaluation of probiotics against red rot disease in Pyropia - Peiwen Weng; Huichao Yang; Zhaolan Mo; Wenbin Zhang; Yongwei Yan; Xiaojun Rong; Jie Li (Aquaculture, 2024)

Tillage after irrigation decreases soil N2O but increases CO2 emissions in a rice-wheat rotation system - Zheng-Rong Kan; Yalin Yu; Amiao Jiu; Zhenzhen Li; Yanling Li; Yifan Li; Yinan Xu; Feng-Min Li; Haishui Yang (Sustainable Production and Consumption, 2024)

Sex-dependent effects of rice cadmium exposure on body weight, gut microflora, and kidney metabolomics based on a mouse model - Jin-Lei Yang; Shan Chen; Jin-Feng Xi; Xin-Ying Lin; Rong-Yue Xue; Lena Q. Ma; Dongmei Zhou; Hong-Bo Li (Science of The Total Environment, 2024)

Insights into current bio-processes and future perspectives of carbon-neutral treatment of industrial organic wastewater: A critical review - Xinzheng Zhang; Yuqin Fan; Tianwei Hao; Rong Chen; Tao Zhang; Yong Hu; Dapeng Li; Yang Pan; Yu-You Li; Zhe Kong (Environmental Research, 2024)

Functional lithiophilic skeleton/evolving lithium sulfide artificial protective layer for dendrite-free Li metal anode - Chenyi Sun; Li Gao; Wanling Rong; Rongkai Kang; Yusen Yang; Jiachang Li; Yanwen Bai; Xuelei Tian; Xiufang Bian (Chemical Engineering Journal, 2024)

Multiscale computational fluid dynamics modelling of spatial ALD on porous li-ion battery electrodes - Zoushuang Li; Yuanxiao Chen; Yufeng Nie; Fan Yang; Xiao Liu; Yuan Gao; Bin Shan; Rong Chen (Chemical Engineering Journal, 2024)

Genome dosage alteration caused by chromosome pyramiding and shuffling effects on karyotypic heterogeneity, reproductive diversity, and phenotypic variation in Zea–Tripsacum allopolyploids - Yingzheng Li; Xu Yan; Mingjun Cheng; Zizhou Wu; Qiyuan Zhang; Saifei Duan; Yong Zhou; Huaxiong Li; Shipeng Yang; Yulin Cheng; Wansong Li; Lulu Xu; et al. (Theoretical and Applied Genetics, 2024)

Predicting the velocity and trajectory of a rockfall after collision considering the effects of slope properties - Shao-Zhen Duan; Guang-Li Li; Xin Yang; Xin-Rong Wei (Natural Hazards, 2024)

Voluntary running wheel exercise induces cognitive improvement post traumatic brain injury in mouse model through redressing aberrant excitation regulated by voltage-gated sodium channels 1.1, 1.3, and 1.6 - Dan Wang; Hui-Xiang Zhang; Guo-Ji Yan; Hao-Ran Zhao; Xiao-Han Dong; Ya-Xin Tan; Shan Li; Min-Nan Lu; Rong Mei; Li-Na Liu; Xu-Yang Wang; Yan-Bin Xiyang (Experimental Brain Research, 2024)
Traumatic brain injury (TBI) leads to disturbed brain discharge rhythm, elevated excitability, anxiety-like behaviors, and decreased learning and memory capabilities. Cognitive dysfunctions severely affect the quality of life and prognosis of TBI patients, requiring effective rehabilitation treatment. Evidence indicates that moderate exercise after brain injury decreases TBI-induced cognitive decline. However, the underlying mechanism remains unelucidated. Our results demonstrate that TBI causes cognitive impairment behavior abnormalities and overexpression of Nav1.1, Nav1.3 and Nav1.6 proteins inside the hippocampus of mice models. Three weeks of voluntary running wheel (RW) exercise treatments before or/and post-injury effectively redressed the aberrant changes caused by TBI. Additionally, a 10% exercise-conditioned medium helped recover cell viability, neuronal sodium current and expressions of Nav1.1, Nav1.3 and Nav1.6 proteins across cultured neurons after injury. Therefore, the results validate the neuroprotection induced by voluntary RW exercise treatment before or/and post-TBI. The RW exercise-induced improvement in cognitive behaviors and neuronal excitability could be associated with correcting the Nav1.1, Nav1.3, and Nav1.6 expression levels. The current study proves that voluntary exercise is an effective treatment strategy against TBI. The study also highlights novel potential targets for rehabilitating TBI, including the Navs proteins.

Characterization of multi-band GNSS multipath in urban canyons using the 3D ray-tracing method - Shaoqian Li; Rong Yang; Xingqun Zhan (GPS Solutions, 2024)